(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article provides information about mesh surfaces, which are the main element of seed cleaning equipment, analyzes information about the designs of mesh surfaces and their mesh geometric shapes and their application in the technological process, and gives recommendations